Clinical recrudescence of chronic untreated P. malariae infection after BNT162b2 CoVID-19 vaccine. (2022) - Ciusa, G.; Guida Marascia, F.; Virruso, R.; Angheben, A.; Guaraldi, G.; Cascio, A.
Abstract: We described a case of clinical reactivation of chronic P. malariae infection following CoVID-19 vaccination with BNT162b2 (Pifzer-Biontech CoVID-19 vaccine) in a 48-year old Italian man.The patient came to our attention for fever of unknown origin show a quartan pattern (every third day) associated to splenomegaly, the onset of the fever occurred one month after CoVID-19 vaccination with BNT162b2. P. malariae was diagnosed using Carestart™ malaria rapid test and Polymerase-Chain Reaction. Post-vaccine transient reduction of immune reactivity is described in literature, although the mechanism is unknown.